MORAL APARATUR SIPIL NEGARA ADALAH GAMBARAN MORAL ANAK BANGSA INDONESIA (PERSPEKTIF AL-QUR’AN) - salmadanis salmadanis (Al Irsyad : Jurnal Bimbingan Konseling Islam, 2018)
The relationship between morality and ASN, is like the relationship between spirit and body. The body without spirit is a carcass and is not meaningful, whereas a spirit without a body is a wild meaning because it does not have a discourse of embodiment. This means that between moral and ASN has a very close relationship. Individuals, as the main and first elements of a society, physically stand alone, but spiritually between individuals have a strong relationship. These strong, spiritual ties are built as a result of natural interactions in various forms and implications. The spiritual relationship is then channeled into language as a medium of communication. It is through this language that various feelings of thought, experience, desires, values and so forth are expressed, developed and inherited, thus giving birth to culture. ASN has and produces innovation and creativity that comes from thoughts, feelings that are all in the moral domain. If further detailed, the form of ASN makes ideas, values, norms and other rules, is the ideal of ASN that gives life to a society called the cultural system. The next manifestation of human actions and behavior, is called a social system, namely the activities of individuals in interacting with each other. Thus, moral on the one hand is in the cultural system and on the other hand is a social system for a society. This further clarifies the relationship between morality and ASN.